Effectiveness of video-only strategies on knowledge regarding self-management of osteoarthritis among osteoarthritis patients visiting tertiary care hospital, Faridkot, Punjab - Kaur, Jaspreet; Kumar, Anil; Kaur, Shaminder; Dahuja, Anshul; Raina, Rohit (International Journal of Research in Orthopaedics, 2026)
Background: Osteoarthritis (OA) is a chronic degenerative joint disorder characterized by pain, stiffness, functional limitation and reduced quality of life. It is the second most prevalent rheumatologic condition worldwide and a leading cause of disability, particularly affecting the knee and hip joints. OA may be classified as primary, commonly associated with aging or secondary, resulting from underlying conditions. The burden of OA is substantial in India, where prevalence ranges from 22–39%, with higher incidence among women and older adults. Globally, OA prevalence has risen markedly over recent decades, emphasizing the need for effective self-management strategies. Aim of the study was to evaluate the effectiveness of video-only educational strategies on knowledge regarding self-management of osteoarthritis among patients. Methods: A pre-experimental one-group pretest–posttest design was employed. The study included 130 osteoarthritis patients attending GGS Medical College and Hospital, Faridkot, Punjab. Knowledge regarding self-management of OA was assessed before and after the intervention. J.W. Kenny’s Open System Model served as the conceptual framework. Data were analysed using descriptive and inferential statistics. Results: Findings demonstrated a significant improvement in participants’ knowledge following the video-based intervention. The mean knowledge score increased from 12.60±4.29 in the pretest to 22.23±3.29 in the posttest, with a mean difference of 9.63. The paired t-test value (t=38.41, p<0.001) indicated high statistical significance. Conclusions: Video-only educational strategies are effective in enhancing knowledge related to self-management among patients with osteoarthritis.